Role of commission receipts in formation of the revenue of the commercial bank - Abramova, A. S.; Fedyshyn, M.F.; Marich, M.G.; Zhavoronok, A.V. (Financial and credit activity: problems of theory and practice, 2019)
The expanding of banking services spectrum allows the redistributing of financial risks, the reduce of their negative impact on the efficiency of the commercial bank and creating of new revenue channels. According to this process, the issues of increasing the volume of provision and growth of commission receipts proportion in the general structure of revenues of banking institutions are actualized. In addition, commission receipts more stable than interest, but their not associated with the risk of losing the value of invested assets (except for the guarantee operations). That is why the article is devoted to determination of the effect of impact the volume of commission of banks on the total amount of their income. The research is based on the study of the relationship between the indicators in deal with cubic one-factor regression model. It would be the basic for a diversification of the portfolio of banking services to protect the bank from crises at the financial market and for adoption of effective management decisions. As a result, the significant influence of the growth of commission receipts on the general level of income of commercial banks. This is evidenced by the computed the correlation coefficient (its value is 0.96 and shows the close relationship between the volume of revenues and volumes of their commission receipts), coefficient of determìnacìï, which is 0.91 (that is change the bank`s income on 91.0% depends on the change in the volume of commission receipts of commercial banks) and strong elasticity ECI(I > 1 (the increase of commission receipts of banks in Ukraine has a significant impact on the growth of their total). According that it is possible to conclude that the role of commissions in the general process of generating revenues of the bank is increased.
Keywords: banking system, banking operations, commission receipts, system approach, modeling, portfolio of banking services